Language Attitudes Of Hokkien Speakers Towards Hokkien and Mandarin - Ting, Su Hie; Puah, Yan Yann (2010)
The paper examined the attitudes of Hokkien speakers towards their vernacular language and Mandarin. The participants for the study were 50 students at a Malaysian university in Kuching, Sarawak who were of Hokkien parentage and spoke Hokkien. Data collected using the matched-guise technique were analyzed using a paired t-test to investigate whether the participants' attitudes towards these two languages were significantly different. The results showed that Mandarin was ranked significantly higher than Hokkien on both status and solidarity dimensions. The study revealed that, based on the participants' subconscious reactions to selected traits examined in the matched-guise technique, participants with a strong Hokkien identity are likely to perceive Hokkien speakers as less educated, having less leadership skills and more humorous than Mandarin speakers. As a group, the participants were found to have closer affinity to Mandarin speakers. The findings have implications on language maintenance efforts of speech communities concerned with diminished affiliation of the younger generation with vernacular languages.